Establishing trust in cross cultural context: a case study of Mamsys. (2015) - Shukla, Sangeeta; Singh, Nimisha
The global business landscape makes communicating with diverse cultures a necessity. Technology has brought distant geographic groups together, but the distance in communication remains. Groups with culturally different customs, traditions and beliefs face difficulties in communicating. The challenge for managers, across the world, is to make their teams communicate in the same cultural language. It thus becomes imperative for business people not only to understand their own communication style and how it might be interpreted, but also to understand and respect the cultural peculiarities of their clients and customers. This case presents the communication challenges faced by Mamsys, an IT company based in India, as it does business with clients from different parts of the world. The case also suggests strategies for communicating effectively while respecting cultural differences. Through this case, an understanding of Indian-Western communications may be facilitated.